2014
DOI: 10.1371/journal.pmed.1001620
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation, Hygiene, and Soil-Transmitted Helminth Infection: A Systematic Review and Meta-Analysis

Abstract: In a systematic review and meta-analysis, Eric Strunz and colleagues examine whether improvements in water, sanitation, and hygiene (WASH) practices are associated with reduced risk of infections with soil-transmitted helminths. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
561
8
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 642 publications
(613 citation statements)
references
References 125 publications
30
561
8
14
Order By: Relevance
“…The findings are supported by previous reviews, which have reported lower prevalence of diarrhea, helminth infections, and trachoma due to improved water access (Esrey et al, 1991;Fewtrell and Colford, 2005;Strunz et al, 2014). Continuous supply, water quality, and storage emerged as mediating factors for health benefits of piped on-plot water, consistent with recent review findings (Wolf et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The findings are supported by previous reviews, which have reported lower prevalence of diarrhea, helminth infections, and trachoma due to improved water access (Esrey et al, 1991;Fewtrell and Colford, 2005;Strunz et al, 2014). Continuous supply, water quality, and storage emerged as mediating factors for health benefits of piped on-plot water, consistent with recent review findings (Wolf et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Increased durations among children of less educated mothers, in turn, may result from such women being less aware of the importance of improved hygiene practices in limiting infection exposure (Wani SA et al, 2007). For A. lumbricoides, the increased infection durations in households with no indoor bathrooms is consistent with reports that poor sanitation facilities increases the risk of A. lumbricoides infections (Strunz EC et al, 2014;Ziegelbauer K et al, 2012). Finally, the association of reduced water access and dirt flooring with increased E. intestinalis trophozoite and fecal cyst counts (Langford TD et al, 2002;Venkatesan et al, 1996).…”
Section: Discussionsupporting
confidence: 60%
“…There were other factors that caused the helminthes infection such as social-economy, sanitary, mother's level of education, the condition of floor in houses, and many others. 6,[10][11][12][13][14] In this study, it has been discovered that in socialeconomy aspect, which was measured through income, 58 (42.3%) out of 137 subjects have income above the average regional payment (Upah Minimum Regional/ UMR) of Sumedang as 1.735.470 rupiahs. From the educational aspect of the mother, 49 (35.8%) and 46 (33.6%) subjects were graduated from junior high school and senior high school.…”
Section: Discussionmentioning
confidence: 99%